2003
DOI: 10.1046/j.1542-474x.2003.08308.x
|View full text |Cite
|
Sign up to set email alerts
|

P Wave Amplitude and Duration may Predict Immediate Recurrence of Atrial Fibrillation After Internal Cardioversion

Abstract: As a result, the incidence of IR of AF after IC was higher in the patients with shorter P wave amplitude (for lead II P<0.01, for V1 P<0.01) and larger P wave duration (for lead II P<0.01, for V1 P<0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…Several studies have shown that prolonged SAPWD can affect the short-term and intermediate prognosis for AF relapse (11,14,17). In a recent AFFIRM-substudy, electrophysiological remodelling evaluated from the standard ECG (lead II P-wave duration135 ms) was associated with an increased risk of recurrent AF within 2 months of cardioversion (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that prolonged SAPWD can affect the short-term and intermediate prognosis for AF relapse (11,14,17). In a recent AFFIRM-substudy, electrophysiological remodelling evaluated from the standard ECG (lead II P-wave duration135 ms) was associated with an increased risk of recurrent AF within 2 months of cardioversion (18).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with analysis of a standard 12-lead ECG, Guidera and Steinberg already in 1993 showed that the SAECG is superior in detection of P wave prolongation as a risk marker of AF (10). Later, prolonged SAPWD has been associated with AF in different clinical settings (11,12). However, the method has not yet been accepted in clinical use (13).…”
mentioning
confidence: 99%
“…Prior studies have demonstrated that individuals with clinical history of paroxysmal AF (PAF) have a significantly longer intra-atrial and inter-atrial conduction time of sinus impulses, which was not only electrophysiologically determined [4,5,6,] but was also shown as P-wave prolongation on 12-lead surface ECG and signal-averaged ECG recordings [7,8,9]. The importance of P-wave dispersion (P d ) in predicting recurrence of AF in patients with PAF and after cardioversion was also elucidated [10,11,12]. But, however, we do not know the predictive value of P d for AF in patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…The cylindrical torso was 50 units in height with major axis diameter of 17 units and minor axis diameter of I3 units, and comprised I96 rectangular elements. The base of the dipole was located 2 units forwards (x), 5 units to the left (y) and 12 units up ( 2 ) from the centre of the cylinder. The model is ilIustrated in figure 1.…”
Section: Single Dipole Modelmentioning
confidence: 99%
“…P wave amplitude has been proposed as a marker for predicting recurrence of atrial fibrillation (AF) after treatment [2], and for identifying pulmonary vein origin of atrial premature complexes [3,4J.…”
Section: Introductionmentioning
confidence: 99%